2021
DOI: 10.1128/mcb.00332-21
|View full text |Cite
|
Sign up to set email alerts
|

Saikosaponin-d Alleviates Renal Inflammation and Cell Apoptosis in a Mouse Model of Sepsis via TCF7/FOSL1/Matrix Metalloproteinase 9 Inhibition

Abstract: Evidence exists reporting that Saikosaponin-d can prevent experimental sepsis, and this study aims to illustrate the molecular events underlying its renoprotective effects on lipopolysaccharide (LPS)-induced renal inflammation simulating sepsis. Through network pharmacology analysis and bioinformatics analysis, we identified that saikosaponin-d may influence sepsis development by mediating TCF7. Dual luciferase reporter gene and ChIP assays were used to explore the interactions between TCF7, FOSL1 and MMP9. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…Transcription factor 7 (TCF7, also known as TCF1) is one of the members of the TCF/LEF transcription factor family and participates in the transcriptional regulation of Wnt/β-catenin signal [ 1 , 3 ]. Emerging evidence has shown that TCF7 is involved in tumorigenesis and development [ 2 , 35 , 44 ], sepsis-induced renal injury [ 39 ], heart development [ 40 ], and cardiac hypertrophy [ 26 ]. However, the roles and underlying mechanism of TCF7 in HLF have not been clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Transcription factor 7 (TCF7, also known as TCF1) is one of the members of the TCF/LEF transcription factor family and participates in the transcriptional regulation of Wnt/β-catenin signal [ 1 , 3 ]. Emerging evidence has shown that TCF7 is involved in tumorigenesis and development [ 2 , 35 , 44 ], sepsis-induced renal injury [ 39 ], heart development [ 40 ], and cardiac hypertrophy [ 26 ]. However, the roles and underlying mechanism of TCF7 in HLF have not been clarified.…”
Section: Introductionmentioning
confidence: 99%
“…FOSL1 serves as the dominant activating protein 1 family member, can promote tumorigenesis in CRC through the FBXL2/Wnt/β-catenin axis [ 52 ]. Furthermore, FOSL1 can regulate inflammation through TCF7/FOL1/MMP9 axis [ 53 ]. Therefore, the main functions of these five core genes are antioxidant stress, anti-inflammatory and detoxification.…”
Section: Discussionmentioning
confidence: 99%
“…Fra-1 affects the differentiation and activation of immune cells, especially macrophages, as well as the secretion of many cytokines ( 17 , 121 , 133 , 138 , 142 , 198 , 199 ), but the specific mechanism remains to be further explored. The regulation of the immune response of Fra-1 makes its intracellular expression affect the outcome of many diseases, such as sepsis ( 149 ), atherosclerosis ( 155 ), myocardial infarction ( 101 ), psoriasis ( 134 ), colitis ( 162 ), etc. This evidence points at the importance of Fra-1 in immune regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Down-regulation of MMP9 can reduce inflammation, while Fra-1 can occupy the promoter of MMP9 ( 170 , 171 ). The silencing of Fra-1 destroys the expression of MMP9 ( 172 ), thereby reducing sepsis-induced renal inflammation and apoptosis ( 149 ). In addition, many studies have found that sepsis in mice overexpressing Fra-1 increases the severity of lung injury ( 150 ).…”
Section: Immune-related Diseasesmentioning
confidence: 99%